(untitled) (Società e diritti, 2018)
The institution of the Ombudsman - based on the idea that citizens should be entitled to complain against specific acts and behaviours of their rulers and that their complaints should be investigated by an independent body - in a new global era play a new role in the defence of individual human rights. The comparison between the Italian case study and the constitutional reform in France demonstrates the activity of the Human Rights Ombudsman is dysfunctional for authoritarian governments and promote a complete democratization of political institutions. Key words: Ombudsman, Human rights, Democratic Institutions